Ultrafast, Single-Event Ptychographic Imaging of Transient Electron Dynamics - Jonathan Barolak; David Goldberger; Bojana Ivanic; David Schmidt; Claudia A. M. Schrama; Charles G. Durfee; Daniel E. Adams (Ultrafast Science, 2024)
Dynamic phenomena occurring on the ultrafast time scales are inherently difficult to image. While pump–probe techniques have been used for decades, probing nonrepeatable phenomena precludes this form of imaging. Additionally, many ultrafast phenomena, such as electron dynamics, exhibit low amplitude contrast in the optical wavelength range and thus require quantitative phase imaging. To better understand the underlying physics involved in a plethora of ultrafast phenomena, advanced imaging techniques must be developed to observe single events at an ultrafast time scale. Here, we present, to the best of our knowledge, the first ptychographic imaging system capable of observing ultrafast dynamics from a single event. We demonstrate ultrafast dynamic imaging by observing the conduction band electron population from a 2-photon absorption event in ZnSe pumped by a single femtosecond pulse. We verify experimental observations by comparing them to numeric solutions of a nonlinear envelope equation. Our imaging method represents a major step forward in ultrafast imaging, bringing the capabilities of ptychography to the ultrafast regime.